Approach to energy efficiency among micro, small and medium enterprises in India : results of a field survey - Ghosh, Duke (UNIDO ViennaAT, 2011)
Explores why there is resistance among MSMEs to accept 'green business' which entails among other things achieving energy efficiency, particularly as the sustainability agenda promotes the competitive advantage of these businesses.